Application of focused ion-beam sampling for sidewall-roughness measurement of free-standing sub-μm objects by atomic force microscopy. (15th January 2020) - Nagatomi, Takaharu; Nakao, Tatsuya; Fujimoto, Yoko
Abstract: In the present study, a free-standing object-sampling technique for microelectromechanical systems (MEMS) is developed to measure their sidewall surface roughnesses by atomic force microscopy (AFM). For this purpose, a conventional focused ion beam (FIB) sampling technique widely used for cross-sectional transmission electron microscope specimen preparation was applied. The sub-nm-order roughness parameters were quantitatively measured for sidewalls of Si-bridge test samples. The roughness parameters were compared before and after H2 annealing treatment, which induced smoothing of the surface by migration of the Si atoms. The reduction in the surface roughness by a factor of approximately one-third with 60-s H2 annealing was quantitatively evaluated by AFM. The present study confirms that the developed FIB–AFM technique is one potential approach for quantitatively evaluating the surface-roughness parameters on the oblique faces of free-standing objects in MEMS devices. Abstract : FIB sampling technique was developed for AFM measurement of side-wall surface roughness of free-standing objects in MEMS devices. We confi rmed that the proposed FIB-AFM technique is one potential and practical approach to quantitatively evaluate surface roughness of oblique faces of free-standing objects in MEMS devices.